How Two Tests Can Help Contain COVID-19 and Revive the Economy - de Walque, Damien (World Bank E-Library Archive, 2020)
Faced with COVID-19 (Coronavirus), countries are taking drastic action based on little information. Two tests can help governments shorten and soften economically costly suppression measures while still containing the novel coronavirus (COVID-19) pandemic. The first-a PCR assay-identifies people currently infected by testing for the presence of live virus in the subject. The second-an antibody test-identifies those rendered immune after being infected by searching for COVID-19-specific antibodies. The first test can help contain the disease because it facilitates the identification of infected persons, the tracing of their contacts, and isolation in the very early stages of an epidemic-or after a period of suppression, in case of a resurgent epidemic. The second can help us assess the extent of immunity in the general population or subgroups, to finetune social isolation and to manage health care resources. Wide application of the two tests could transform the battle against COVID-19 (Coronavirus), but implementing either on a large scale in developing countries presents challenges. The first test is generally available, but needs to be processed in adequately equipped laboratories with trained staff. The second test is easy to perform and can be processed quickly on the spot, but at this stage it is produced and available only on a limited basis in a few countries. This policy brief reviews the use of both tests, suggests strategies to target their use, and discusses the benefits and costs of such strategies. If PCR assay testing, together with tracing and isolation, helps reduce the duration of suppression measures by two weeks, and antibody testing allows one-fifth of the immune return to work early, the gain could be about 2 percent of national income, or about